Orally administered Î²- glucan of edible mushroom (Pleuratus florida) origin upregulates innate immune response in broiler - Paul, I; Isore, D P; Joardar, S N; Samanta, I; Biswas, U; Maiti, T K; Ganguly, S; Mukhopadhyay, S K (The Indian Journal of Animal Sciences, 2012)
With the aim of assessing the effect of purified Î²-glucan from an edible mushroom (Pleuratus florida) as an immunomodulator on the innate immune responses in broiler chicken (40), purified mushroom glucan was administered orally to 1-week-old broiler chicks (20) @ 20 mg/kg feed for 15 days and then switch back to control diet. Similar number of birds were kept separately as control with normal feeding regime. Non-specific immunity and protective ability were assessed in treated and control birds at the end of the experimental feeding period (0 day) by performing neutrophil, macrophage and lymphocyte functional assay in vitro and challenged with virulent field isolate of Ranikhet disease. Superoxide anion production by neutrophil, in vitro non-specific lymphoproliferation and IL-2 production were increased gradually up to 10 days post treatment and the increase was highly significant (P<0.05) compared to control birds. In vitro nitrite production by macrophage was found to be high in treated birds. Also mushroom glucan as a feed supplement significantly provided protection against Ranikhet disease. The result showed the potentiality of Î²-glucan (mushroom origin) as an immunostimulant in poultry.